LIGHT SCATTERING IN RESEARCH AND QUALITY CONTROL OF DEUTERIUM DEPLETED WATER FOR PHARMACEUTICAL APPLICATION - KOLDINA, A. M.; USPENSKAYA, E. V.; BORODIN, A. A.; PLETENEVA, T. V.; SYROESHKIN, A. V. (International Journal of Applied Pharmaceutics, 2019)
Objective: Development of a methodology for measuring the deuterium content in water for pharmaceutical purposes by laser light scattering based on ideas about the cluster structure of water. Methods: Samples of industrially manufactured drinking water from different manufacturers with varying deuterium content from 10 ppm to 115 ppm. For the titration of laboratory samples of deuterium depleted water in increments of 5 ppm the following reagents were used: Water, deuterium-depleted (≤1 ppm (D2O, Aldrich, USA); Deuterium oxide/Heavy water/Water-d2 (99.9 atom % D, Aldrich, USA); water Milli-Q (specific resistance 18.2 µS·sm at 25 оС, ТОС ≤ 5 ppb, Merck Millipore). The determination of deuterium content in samples of industrially manufactured water and water obtained in a laboratory manner was carried out by the method of low-angle laser light scattering (LALLS) at the Mastersizer (Malvern Instruments) analyzer and using a working measuring tool–laser dispersion meter/MDL («Cluster-1», Russia/Ukraine). The statistical methods–packages OriginPro®9. Results: It was found that the content of isotopologies in water leads to physicochemical water’s properties changes and morphology changes of giant heterogeneous clusters (GHC). The results of low-angle laser light scattering (LALLS) in the water samples under investigation showed the dependence of the water GHC "dispersibility" expressed in the differentiation of curves of the volume size distribution ("size spectra"), the volume concentration, w%, the laser obscuration values (I ‒I0) as the function of the water isotopic composition variations. The laser diffraction method results correlate with two-dimensional (2D) multi-descriptor mathematical analysis. Conclusion: When identifying deuterium depleted water, it should be considered not only the indicators that determine its pharmacopoeial quality, but also the D/H ratio, because even small changes in the natural isotopic composition of water lead to significant biological effects. Our proposed approach using laser diffraction in combination with mathematical apparatus of (2D) multi-descriptor laser scattering analysis makes possible the exact calculation of individual signs of deuterium depleted water as the pharmaceutical object of study.